Focal adhesion kinase promotes phospholipase C-γ1 activity - Zhang, Xiaoe (The National Academy of Sciences, 1999)
The nonreceptor tyrosine kinase FAK (“focal adhesion kinase”) is a key mediator of integrin signaling events controlling cellular responses to the extracellular matrix, including spreading, migration, proliferation, and survival. Integrin-ligand interactions stimulate FAK tyrosine phosphorylation and activation of FAK signaling functions. Here evidence is presented that the FAK autophosphorylation site Tyr-397 mediates a direct interaction with the C-terminal Src homology 2 domain of phospholipase C (PLC)-γ1 and that this is required for both adhesion-dependent association of the two molecules and increased inositol phosphate production in mouse embryo fibroblasts. Overexpression of FAK and PLC-γ1 in COS-7 cells increases PLC-γ1 enzymatic activity and tyrosine phosphorylation, also dependent on FAK Tyr-397. However, FAK appears incapable of directly phosphorylating PLC-γ1. These observations suggest a role for FAK in recruiting PLC-γ1 to the plasma membrane at sites of cell-matrix adhesion and there promoting its enzymatic activity, possibly by releasing the repression caused by intramolecular interactions of the PLC-γ1 Src homology domains and/or by positioning it for phosphorylation by associated Src-family kinases. These findings expand the known signaling functions of FAK and provide mechanistic insight into integrin-stimulation of PLC-γ1.